Pengembangan Aplikasi Keuangan Berbasis Web Menggunakan Laravel Filament di PT Kargo Transkontinental - Retno Utami, Tri; Galet Guntoro Setiaji; Rifa'i, Ahmad (Universitas Boyolali, 2025)
PT Kargo Transkontinental, as a company engaged in the field of freight forwarding with a high transaction volume, faces significant operational challenges due to its reliance on manual financial recording processes. This dependence leads to delays in the preparation of financial reports, which can take up to two working days, and carries a potential error rate of up to 10% in cost recording. Such conditions pose a major obstacle to conducting accurate and timely profitability analysis. This study aims to design and develop a web-based financial application using the Laravel Filament framework to overcome these inefficiencies. To ensure a systematic development process, the research adopts the waterfall development method, which consists of the stages of requirements analysis, design, implementation, testing, and maintenance. System requirements were gathered through direct interviews with the company's finance division. The study produced a functional web application that successfully integrates modules for employee income, expenses, and loans, further enhanced with an innovative digital receipt feature to bolster accountability. The application features role-based access control for superadmins and staff and offers centralized reporting capabilities. In conclusion, the developed application streamlines the job costing process, elevates data accuracy, and accelerates financial reporting, thereby supporting more effective decision-making.